CCAFS Program of Work and Budget 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The 2015 program of work and budget of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) lays out the key activities and budget in 2015.